The Demand for Money During High Inflation Episodes : Some Latin American Evidenceon the Cagan Model - Taylor, Mark (IMF Working Papers; Working Paper, 1991)
This paper examines the demand for money under conditions of very high inflation in Argentina, Bolivia, Brazil, Chile and Peru during the 1970s and 1980s. We test whether the monetary and inflationary experiences of these countries can be adequately characterized by the Cagan (1956) model, using an econometric procedure which is not reliant on any particular assumption concerning expectations formation except that forecasting errors are stationary. We also examine the importance of foreign asset substitution in domestic portfolios.